Study the Attenuation Coefficient of Granite to Use It as Shields against Gamma Ray - Najam, Laith A.; Hashim, Abdalsattar K.; Ahmed, Hussein A.; Hassan, Israa M. (Scientific Research Publishing, 2016)
The present work investigates the linear and mass attenuation coefficients for gamma rays practically and theoretically by using spectroscopy gamma ray (UCS-20) and program (XCOM)) for various types of common use granite, and compares them with the lead because of its high blocking ability for this type of radiation. This paper concluded through linear and mass attenuation coefficients measurements that these coefficients decrease with increasing incident photons energy. Measurements also showed that the linear attenuation coefficients appropriate linearly with density while mass attenuation coefficients do not get affected.
Keywords: Gamma Rays; Attenuation Coefficient (Linear and Mass); Building Materials; Sodium Iodide Detector